The Influence of Service Quality on Patient Satisfaction at the Klinik Pratama Rawat Inap Siti Zachroh - Nuria, Anisya Intan; Fa’uzobihi,, Fa’uzobihi,; Partimah, Partimah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The main problem of Klinik Pratama Rawat Inap Siti Zachroh is the lack of service quality caused by human resources, facilities, and referrals that have not been optimal yet. The research aims to analyze the influence of service quality on patient satisfaction. The method of the research is the quantitative approach with associative method to analyze two variables, namely service quality and patient satisfaction. The results of the research indicate that the validity and reliability tests are valid and reliable with value of r table 0.349. The results of questionnaire data processing and the answers of respondents regarding service quality show the effective criteria 62,1%. The t test indicates that value of t > t table is obtained (6,770 > 2,048). It means that there is partially a significant influence of service quality on patient satisfaction, then Ho is rejected. The correlation analysis of R obtains 0.788, indicating that there is a strong relationship of service quality to patient satisfaction. The result of coefficient determination obtains R square score 0.621 or 62,1%, therefore the contribution percentage of service quality variable to patient satisfaction variable is 62,1%, included in the high effective criteria. The conclusion is that there is a strong influence of service quality on patient satisfaction in Klinik Pratama Rawat Inap Siti Zachroh.